Environmental burdens of producing bread wheat, oilseed rape and potatoes in England and Wales using simulation and system modelling - Williams, Adrian G.; Audsley, Eric; Sandars, Daniel L. (Ecomed Publishers, 2010)
Background, aims and scope Food production is essential to life. Modern farming uses considerable resources to produce arable crops. Analysing the environmental burdens of alternative crop production methods is a vital tool for policymakers. The paper describes the production burdens (calculated by life cycle analysis) of three key arable crops: bread wheat, oilseed rape and potatoes as grown in England and Wales using organic and non-organic (contemporary conventional) systems. Resource use (e.g. abiotic and energy) and burdens from emissions are included (e.g. global warming potential on a 100-year basis, global warming potential (GWP), and eutrophication and acidification potentials). Methods Crop production was analysed, using systems models, so that the effects of factors like changing N fertiliser application rates or irrigation could be examined. Emissions of nitrate were derived from a simulation model in which soil organic N was driven to steady state so that all long-term effects were properly accounted for. Yield response curves to N were similarly derived from long-term experiments. Crop nutrient inputs and plant protection applications were derived from national survey data and the literature. All major inputs were accounted for including fertiliser extraction, manufacture and delivery; pesticide manufacture; field fuel use; machinery and building manufacture; crop drying, cooling and storage. The current balance of production systems were found from survey data. The weighted mean national production was calculated froma combination of three rainfall levels and soil textures. The system boundary is the farm gate. The functional unit is 1 t marketable fresh weight of each product. Results and discussion The primary energy needs for the producing the three main crops were 2.4, 4.9 and 1.4 GJ/t for bread wheat, oilseed rape and potatoes, respectively. When expressed in terms of dry matter, protein or energy, wheat incurred smaller burdens than oilseed rape, which incurred lower burdens than potatoes. The crops do, of course, all play different roles. Organically produced bread wheat needed about 80% of the energy of non-organic, while organic potatoes needed 13% more energy than nonorganically produced ones. While pesticide use was always lower in organic production, other burdens were generally inconsistently higher or lower. Land occupation was always higher for organic production. Lower fertiliser use (and hence energy use) in organic systems is offset by more energy for fieldwork and lower yields. Main crop potato energy needs are dominated by cold storage. Reducing the N application rate for bread wheat production reduces energy use and GWP. The optimum for energy is with N at about 70% of the current level. It seems to be lower for GWP, but the sub-models used are beyond their range of reliability. The results are generally of the same order as those from other European studies. Conclusions Arable crop production depends heavily on fossil fuel in current major production systems. The emissions causing GWP are very dependent on nitrous oxide, more so than fuel consumption. That, together with emissions of ammonia and nitrate, means that agriculture has a C-N footprint rather than the C footprint that typifies most industrial life. Recommendations and perspectives With the large influence of nitrous oxide on GWP, evaluation of nitrous oxide emissions by another method, e.g. crop-soil simulation modelling instead of the more rigid IPCC method would improve the robustness of the analysis. The transition betweenfarming systems was not included in this study, but there could be short to medium term benefits of converting from nonorganic to organic methods that should be evaluated. System modelling allows alternative production methods to be readily explored and this greatly enhances LCA methodology.